Letter from Henry M. Morfit to James Curtis Booth, September 9, 1850 - Morfit, Henry Mason (1850)
Henry M. Morfit (1793-1865), a claims lawyer in Washington, D.C. and a political figure in the Andrew Jackson presidential administrations, appears to have served as go-between for his son, Campbell Morfit (1820-1897), and James Curtis Booth (1810-1888) in their efforts to interest the U.S. Mint in their process for refining gold. In this letter, Morfit remarks on Booth and Campbell’s application sent on to the Director of the Mint.
Keywords: United States Mint; Mint of the United States; Booth, James Curtis, 1810-1888; Metals--Refining; United States. Assay Office, New York City; Morfit, Campbell, 1820-1897; Patents